Techno-poetics in micro-stories of the digital age: The case of Alex Epstein. - Levin, Orna (Digital Scholarship in the Humanities, 2020)
In this study, I frame the concept of techno-poetics by analyzing Alex Epstein's micro-stories and by examining the development of the micro-fiction genre throughout the world. Epstein is a contemporary Israeli author whose universal micro-stories have been translated into several languages (English, Spanish, French, and Russian). Epstein uses a dual language: given his career as a computer programmer in a high-tech company, the language of his thoughts is conveyed through the logic of technology, whereas, as an artist, he is loyal to the language of poetics. Is Epstein a "programmer" of micro-stories? Within the framework of this study, I analyze the dynamic relationship between the polar opposites of technology and poetics, as it is revealed in Epstein's micro-stories, taking into account the genre's characteristics as well as the unique features with which Epstein—as a contemporary author—imbues his works. More specifically, I analyze six categories that describe the relationship between digital technology and the world of art, a relationship that informs Epstein's micro-stories. Epstein's work was not created in a void; nevertheless, his micro-stories differ not only from the works of previous authors of the genre, but also from those of his contemporaries, whose work, likewise, deals with the tension between technology and poetics. A major difference is the methods of publication that Epstein uses, which form part of the techno-poetical process. In this sense, the themes, the conception of art, and the method of publication are all indications of a unique artistic phenomenon.